ASSOCIATION OF PROPROTEIN CONVERTASE SUBTILISIN/KEXIN TYPE 9 WITH HYPERTENSION AND SMOKING - K. S. Benimetskaya; M. P. Yachmeneva; S. V. Astrakov; L. V. Shcherbakova; D. V. Denisova; Yu. I. Ragino; M. I. Voevoda (Инновационная медицина Кубани, 2019)
Objectives. To estimate the relationship of proprotein convertase subtilisin/kexin type 9 (PCSK9) level with blood pressure (BP) and smoking in a population of young males in Novosibirsk.Material and methods. The group was formed by the method of random numbers from the population sample of  Novosibirsk that underwent a one-time survey as part of the screening «Monitoring of health status and prevalence of risk factors of therapeutic diseases, their prediction and prevention in Siberia». The study included 492 males, the average age was 36.0 ± 5.86 years. Levels of PCSK9 were determined with ELISA using a test system «Human PCSK9 ELISA» (BioVendor, Czech Republic).Results. The average level of the PCSK9 protein was 325.9 ± 141.97 ng/ml, median (interquartile range) was 300.19 (240.20; 361.80). Mean systolic BP was 126.13 ± 13.40 mm Hg, mean diastolic BP was 82.91 ± 9.93 mm Hg. Fifety-six percent (277 males) was non-smokers, 44% (214 males) smoked. PCSK9 levels were higher in sample of smokers (339.49 ± 139.86; 311.82 (251.04; 369.78)) than in sample of non-smokers (315.17 ± 143.16; 286.16 (229.91; 351.71)) (p = 0.011), samples were independent. There was no difference in the level of PCSK9 protein in a pair of samples contrasting in BP. A weak statistically significant correlation between the level of PCSK9 and smoking (rs = 0.115, p = 0.01) was shown, it was indirectly confirmed by the result of multiple regression analysis. Hypertension was an independent predictor of higher levels of PCSK9 protein according to multivariate linear regression analysis using a stepwise method (B = 32.593; SE = 14.624; p = 0.026). Also hypertension was an independent predictor of a higher level of PCSK9 protein according to multivariate linear regression analysis using the backward method in the same model (B = 30.457; SE = 14.649; p = 0.038).Conclusion. The presence of hypertension indicates an increased level of PCSK9. The obtained data support the role of PCSK9 in the pathogenesis of cardiovascular diseases and the prospect of its use as a biological marker. Present study was the first one of such category in Russia.